1977
DOI: 10.1128/aem.33.6.1284-1286.1977
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of bacteria into meat

Abstract: Bacteria are confined to the surface of meat during the logarithmic phase of growth. When proteolytic bacteria approach their maximum cell density, extracellular proteases secreted by the bacteria apparently break down the connective tissue between muscle fibers, allowing the bacteria to penetrate the meat. Non-proteolytic bacteria do not penetrate meat, even when grown in association with proteolytic species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
2

Year Published

1978
1978
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 4 publications
2
25
0
2
Order By: Relevance
“…IN CONTRAST to a recent report (Gill and Penney, 1977) that collagen hydrolysis was a prerequisite for bacterial penetration into meat, results of our work showed bacterial penetration not to be a function of the collagenase activity present in proteolytic enzymes.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…IN CONTRAST to a recent report (Gill and Penney, 1977) that collagen hydrolysis was a prerequisite for bacterial penetration into meat, results of our work showed bacterial penetration not to be a function of the collagenase activity present in proteolytic enzymes.…”
Section: Discussionsupporting
confidence: 78%
“…Later, Elmossalami and Wassef (1971) showed that fresh intact, frozen, and cooked meats were susceptible to invasion by certain strains of pathogenic bacteria even in the absence of an added protease. More recently, Gill and Penney (1977) corroborated the findings that certain bacteria were capable of invading fresh animal tissue in the absence of an added protease.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…VERY RAPID SURFACE HEATING and cooling of meat surfaces has been achieved, using steam and vacuum. This may be useful because the toxic microorganisms of intact meat are usually on its surface (Gill and Penney, 1977). This is true of enterobacteria, such as Salmonella, whose origin is the GI tract of living animals (Bailey et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…B ACTERIA ARE NOT NORMALLY PRESENT IN THE INTERIOR OF healthy, fresh chicken meat. Bacteria are in the pores and crevices of the flesh and skin on the surface of chicken flesh (Gill and Penney 1977). Some of the bacteria are nonpathogenic, spoilage organisms and some are pathogenic.…”
Section: Introductionmentioning
confidence: 99%